Acetate‐ vs lactate‐buffered crystalloid solutions: Protocol for a systematic review with meta‐analysis and trial sequential analysis. Issue 1 (23rd September 2020) - Ellekjaer, Karen Louise; Perner, Anders; Sivapalan, Praleene; Hylander Møller, Morten
Abstract : Background: Buffered crystalloid solutions are increasingly recommended as first‐line resuscitation fluids. However, guidelines do not distinguish between different types of buffered solutions. The aim of the outlined systematic review is to summarize and assess the effects of acetate‐ vs lactate‐buffered crystalloid solutions on patient‐important outcomes. Methods: We will conduct a systematic review of randomized clinical trials (RCTs) with meta‐analysis and trial sequential analysis comparing the use of acetate‐ vs lactate‐buffered crystalloid solutions in hospitalized patients. We will systematically search the Cochrane Library, MEDLINE, EMBASE, and Epistemonikos for relevant literature. We will follow the recommendations set by the Cochrane Collaboration and the Preferred Reporting Items for Systematic Review and Meta‐Analysis (PRISMA) statement. The risk of systematic errors (bias) and random errors will be assessed, and the overall quality of evidence will be evaluated using the Grading of Recommendations Assessment, Development, and Evaluation (GRADE) approach. Discussion: The outlined systematic review will provide important data on how patient‐important outcomes are affected by intravenous administration of acetate‐ vs lactate‐buffered crystalloid solutions in hospitalized patients.